Borrowing costs and the demand for equity over the life cycle - Steven J. Davis; Felix Kubler; Paul Willen (Federal Reserve Bank of Boston, 2005)
We construct a life-cycle model that delivers realistic behavior for both equity holdings and borrowings. The key model ingredient is a wedge between the cost of borrowing and the risk-free investment return. Borrowing can either raise or lower equity demand, depending on the cost of borrowing. A borrowing rate equal to the expected return on equity - which we show roughly matches the data - minimizes the demand for equity. Alternative models with no borrowing or limited borrowing at the risk-free rate cannot simultaneously fit empirical evidence on borrowing and equity holdings.
Keywords: D91; G11; 330; Verbraucherausgaben; Portfolio-Management; Aktie; Lebenszyklus; Theorie